Distribuição de fósforo, potássio e enxofre no solo em função do modo de aplicação dos fertilizantes na cultura da soja - Silva, Eduardo Vaz da (2016)
The Brazil ranks as the world's second largest soybean producer with 96 million tonnes in the 2014/2015 crop, the fact that in cerrado soils is only possible with good soil management system. The aim of this study was to evaluate the fertilizer application methods for soybean and its influence on concentration of nutrients in the soil profile, the biometric parameters and soybean productivity. The study area comprises the 3rd year of soybean cultivation as the main crop with broadcast fertilization in all crop plantations 13/14, succession to the corn crop, and previously the area remained fallow. Located in Deciolândia MT under a dystrophic red Latosol the experiment was conducted considering five seeding bands in randomized block design, factorial arrangement with five replicates and four depths (0 to 0,05 m, 0.05 to 0,01 m, 0,01 to 0,15 and 0,15 to 0,20 m) which were evaluated five treatments: control (without application); K + P in the groove the haul; P and K in the groove; P + K groove the haul; P and K to haul. The phosphate fertilizer when planting furrow favored the availability of P in the soil. As for potassium fertilization did not observe differences in fertilization system. Higher soybean yields were obtained when the P was applied in the planting furrow